Grassroots action research and the greater good (2011)
This study examines the action research topics and topic preferences of two groups of grassroots teachers: active researchers, and potential researchers. The analysis of the topics appears to indicate that, over the past decade, action research at the teaching of English at the grassroots level to speakers of other languages has been principally understood in terms of professional development with respect to teachers’ methodologies and learners’ learning behaviours. A nascent concern for a more ample approach to professional development and issues conducive to the greater good of the profession can, it is mooted, flourish only with the collaboration of all relevant stakeholders.En este estudio se examinan los temas de investigación acción y los temas preferidos por dos grupos de profesores de base: uno de investigadores activos y otro de investigadores potenciales. El análisis sugiere que, durante la última década, la investigación acción en el aula de inglés para hablantes de otras lenguas se ha entendido principalmente en términos del desarrollo profesional con respecto a las metodologías de los profesores y las conductas estudiantiles de aprendizaje. Se considera que un incipiente interés por un enfoque más amplio y por asuntos conducentes al beneficio general de la profesión, solamente puede florecer con la colaboración de todos los actores más importantes.